Investigating photochromic behavior of organic dyes in solution form using multilevel factorial design - Nadir, Najiah; Wahid, Zaharah; Shafie, Amir Akramin; Ahmad, Farah; Zainuddin, Mat Tamizi (Diponegoro University, 2021)
Photochromic compounds, namely spiropyran, spirooxazine, and naphthopyran, have received much attention, be-cause of their high potential applications in various industrial fields. The aim of this study is to understand the be-havior of three photochromic dyes in solution form via statistical approach. The types of dyes and solvents were screened using multilevel factorial design. From the analysis of variance results, it was found that the types of dyes and solvents used as well as their interaction have significant effects on the absorbance and photostability. The naphthopyran compound displayed highest change in absorbance intensity, followed by spiropyran and spi-rooxazine, when dissolved in isopropanol separately. However, the spirooxazine is the most photostable dye com-pared to naphthopyran and spiropyran, with ethanol as the solvent.